The impact of solar elevation angle on the net radiative effect of tropical cyclone clouds - Liang Hu; Dae-Hui Kim; J. Scott Tyo; Elizabeth A. Ritchie (npj Climate and Atmospheric Science)
Abstract In this study solar elevation angle is shown to have a dominant impact on the net radiation due to tropical cyclone (TC) clouds. As solar elevation angle increases, net cooling effects from TC clouds dominate over net warming effects. From 2001 to 2020, the radiative effect of TC clouds remained stable. However, because of the strong dependency on solar elevation angle, future changes in seasonal occurrence could affect this contribution.